(3GdJYKjQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO JbOe dfG bHd gPG KdGKI cJH ef GdJaSjQ deG eVi ef cJHfG GdSHYjf s
(3BNQgG (B:s
(3Hd jfHZi Cf JYde Cf GdJOHjQ dgPg GdKdGKI WQb ef LejY CLfGS GdYGde GdehLhOGJ Gdbhd ai hGMO efgG hGdbhd ai Gdcd HefRdI aGYQag s
(3Vef eLehY , JQJjHgG (B: 44s
(3YfGhjf GdcJH ef GdebGdI GdQGHYI hGdCQHYhf Edi GdNeSjf dGJhLO ai GdCUd hecGfgG HjGVs
(3hQOJ cPdc ai Qbe (B96 (3hgh GdebGdI GdQGHYI hGdCQHYhf ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
Keywords: (3GdcjejGA h GdWHjYjGJs